(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Skintific products have gained high popularity among young consumers, especially through online sales on e-commerce platforms like Shopee. This research aims to determine the influence of promotion, product price, and product quality on consumer purchasing decisions on the Shopee e-commerce platform. The study uses a quantitative approach, with a descriptive associative design, to examine the relationship between the independent variables (promotion, price and product quality) and the dependent variable (purchasing decisions). The research population consists of all Skintific consumers, and the sample size is 91. The study hypothesizes that promotional activities, product pricing, and product quality have a significant influence on purchasing decisions. The study also examines the specific effects of each variable on purchasing decisions, including the impact of promotional activities on increasing consumer interest and desire to purchase a product, the influence of product pricing on consumer purchasing decisions, and the effect of product quality on consumer purchasing decisions. The study’s methodology includes a survey of consumers who have purchased skincare products on Shopee, with a focus on the relationship between the independent variables and the dependent variable This research is expected to provide insights into the factors that influence consumer purchasing decisions on the Shopee e-commerce platform.